THE ROLE OF SALAWATI FERRY PORT ON ACCESSIBILITY AND ECONOMIC ACTIVITIES OF CENTRAL SALAWATI DISTRICT, RAJA AMPAT REGENCY - Muh. Akhsan Samaila; M.M. Lanny W. Pandjaitan; Lukas (SOSCIED, 2026)
Central Salawati District, Raja Ampat Regency faces connectivity and accessibility challenges characterized by dependence on traditional sea transportation with low shipping safety aspects and limited carrying capacity. In response to these problems, the government built the Salawati Ferry Port to support the implementation of ferry transportation. Then, this study analyzes the role of the ferry port on accessibility and economic activity in Central Salawati District using qualitative descriptive methods with operational data from January 2025 to April 2026. The results show that the existence of the Salawati Ferry Port is able to improve accessibility and inter-island connectivity characterized by increased population mobility, improved shipping safety aspects, and reduced costs and travel time compared to traditional sea transportation modes. Economically, the Salawati Ferry Port encourages the distribution of goods, facilitates the distribution of commodities and logistics, and expands public access to educational facilities, health, and government services in Sorong City. Thus, the Salawati Ferry Port plays a strategic role as a transportation hub and driver of the regional economy.